CARDIAC ASTHMA - Kuchiboev Samandar Ismatulla Ogli; Oralov Dilshod Hamid Ogli; Mirzaqulov Sardor Ulug‘Bek Ogli; Ximmatov Jamshid Alisher Ogli (Scholar Express Journals, 2025)
Cardiac asthma is an acute manifestation of left ventricular heart failure characterized by pulmonary interstitial and alveolar edema. It presents clinically with sudden onset dyspnea, orthopnea, tachycardia, and cyanosis. This article discusses the key etiological factors, clinical features, differential diagnosis, and resuscitative management of cardiac asthma
Keywords: cardiac asthma; left ventricular failure; pulmonary edema